2013
DOI: 10.1002/anie.201308657
|View full text |Cite
|
Sign up to set email alerts
|

High‐Yield Electrochemical Production of Formaldehyde from CO2 and Seawater

Abstract: The catalytic, electrocatalytic, or photocatalytic conversion of CO2 into useful chemicals in high yield for industrial applications has so far proven difficult. Herein, we present our work on the electrochemical reduction of CO2 in seawater using a boron-doped diamond (BDD) electrode under ambient conditions to produce formaldehyde. This method overcomes the usual limitation of the low yield of higher-order products, and also reduces the generation of H2 . In comparison with other electrode materials, BDD ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
244
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(260 citation statements)
references
References 23 publications
7
244
2
7
Order By: Relevance
“…In an effort to introduce CO 2 RR active sites with low onset potentials, doping of boron and nitrogen into nanodiamond materials has recently been studied for CO 2 RR application. [92,93] As shown in Figure 8a, N-doped nanodiamond (NDD) was deposited on a silicon rod array using a microwave plasma enhanced CVD method and applied directly as an electrocatalyst for CO 2 reduction. [92] The CO 2 RR onset potential was -0.36 V vs RHE and it was found that the NDD could preferentially produce acetate under any applied potential within the CO 2 RR potential range.…”
Section: Nanodiamond and Glassy Carbonmentioning
confidence: 99%
“…In an effort to introduce CO 2 RR active sites with low onset potentials, doping of boron and nitrogen into nanodiamond materials has recently been studied for CO 2 RR application. [92,93] As shown in Figure 8a, N-doped nanodiamond (NDD) was deposited on a silicon rod array using a microwave plasma enhanced CVD method and applied directly as an electrocatalyst for CO 2 reduction. [92] The CO 2 RR onset potential was -0.36 V vs RHE and it was found that the NDD could preferentially produce acetate under any applied potential within the CO 2 RR potential range.…”
Section: Nanodiamond and Glassy Carbonmentioning
confidence: 99%
“…In this context, carbon-based metal-free catalysts have also been used for CO 2 RR. Figure 11 and Table 1 represent recent advances in the development of carbon-based metal-free catalysts for CO 2 RR [36,37,[207][208][209][210][211][212][213][214].…”
Section: Carbon-based Metal-free Catalysts For Comentioning
confidence: 99%
“…Along with N-doped carbon fibers and CNTs, borondoped graphene (BG) has also been studied for the reduction of CO 2 to formate [207]. Even boron-doped diamonds (BDD) have been demonstrated to show promising catalytic activity for the reduction of CO 2 to methanol, despite diamonds being often considered chemically inert [208]. Here, it was found that sp 3 -bonded carbons on BDD can act as active sites for CO 2 RR.…”
Section: Carbon-based Metal-free Catalysts For Comentioning
confidence: 99%
“…Furthermore, Nakata et al [8] reported that the use of boron-doped diamond (BDD) electrodes in the reduction of CO2 can produce formaldehyde. BDD is reported to be abetter electrode compared to the previous electrode used in this aplication, because it generates higher products percentage.…”
Section: Introductionmentioning
confidence: 99%